ANALISIS DISTRIBUSI SPASIAL DAN KINERJA PELAYANAN KANTOR POS DI KOTA SURAKARTA - Permata Dewi, Anggraini Putri (Pendidikan Geografi, 2015)
ABSTRACTThe research aims at providing: (1) the spatial distribution of the post office (2) the pattern distribution of the post office (3) the perfomance of the post office in Surakarta city in 2012.Spatial descriptive method was applied, the research populations was post office in Surakarta city. Purposive sampling is used as sampling technique to determine the performance of the post office . The data were collected using documentation technique, direct observation of the post office, and questioner to determine the performance of the post office. Map analysis was applied to determine the result.The result of this research reveals: (1) Total post office in Surakarta city are 16 units. The highest distribution of post office in Surakarta is located in Laweyan, they are 6 units (37,5,%), Banjarsari and Jebres are 3 units (18,75%), and the lowest distribution is located in Pasar Kliwon and Serengan, they are 2 units (12,5%). (2) Distribution pattern of post offices in Surakarta is random with value of T=1.41.(3) The best performance post office?s service is at Gladak post office, pretty good service performance are Nusukan post office, Mojosongo post office, UNS post office, Jebres post office, Semanggi post office, Pasar Jongke post office, Gading post office, Tipes post office, Kerten post office and Jajar post office, poor service performance is Cengklik post office, Setabelan post office, Makamhaji post office, Purwosari post office and post office Sriwedari. Keywords: spatial distribution, distribution pattern, performance of services